2015
DOI: 10.1007/s11829-015-9376-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing grasshopper (Orthoptera: Acrididae) communities in sown margin strips: the role of plant diversity and identity

Abstract: Grasshoppers are important components of grassland invertebrate communities, particularly as nutrient recyclers and as prey for many bird species. Sown margin strips are key features of agri-environmental schemes in European agricultural landscapes and have been shown to benefit grasshoppers depending on the initial sown seed mixture. Understanding the mechanisms by which the sown mixture impacts grasshoppers in sown margin strips is the aim of our study. Here, we investigated plantgrasshopper interactions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…They have a considerable importance as primary consumers, nutrient recyclers and constitute the bulk of the diet of many birds in farmlands (Bretagnolle et al 2011). The functional diversity of grasshopper communities is a key driver of their impact on plant communities (Deraison et al 2015b) and is highly sensitive to the composition of local plant communities (van der Plas et al 2012;Badenhausser et al 2015). Strong matching between the strength of grasshopper mandibles (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…They have a considerable importance as primary consumers, nutrient recyclers and constitute the bulk of the diet of many birds in farmlands (Bretagnolle et al 2011). The functional diversity of grasshopper communities is a key driver of their impact on plant communities (Deraison et al 2015b) and is highly sensitive to the composition of local plant communities (van der Plas et al 2012;Badenhausser et al 2015). Strong matching between the strength of grasshopper mandibles (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These grasshoppers are known to prefer moist areas and semi-aquatic habitats like marshes, margins of waterbodies and floodplains. Amédégnato and Devriese (2008) considered most species of pygmy grasshoppers as limno-terrestrial that require an aqueous matrix (moist areas) in strictly terrestrial habitats while some are more dependent on water (such as for egg laying and nymphal development). They appear to be good swimmers and/ or divers (Paranjape et al 1987, Gröning et al 2007, Amédégnato and Devriese 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Amédégnato and Devriese (2008) considered most species of pygmy grasshoppers as limno-terrestrial that require an aqueous matrix (moist areas) in strictly terrestrial habitats while some are more dependent on water (such as for egg laying and nymphal development). They appear to be good swimmers and/ or divers (Paranjape et al 1987, Gröning et al 2007, Amédégnato and Devriese 2008. Different levels of dependency on water correspond to varying degrees of adaptations to swimming, including expanded hind tibia with reduced spines in more water dependent species (Amédégnato and Devriese 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant species composition has been shown to affect the species richness and abundance of arthropods (cf. Altieri, ; Badenhausser, Gross, Cordeau, Bruneteau, & Vandier, ; Dassou et al., ; Ebeling, Klein, Weisser, & Tscharntke, ; Huelber, Haider, Hager, Dullinger, & Fiedler, ; Woodcock & Pywell, ). Schaffers, Raemakers, Sykora, and Ter Braak () reported that plant species composition was the best predictor for an assemblage of different arthropod taxonomic groups and families.…”
Section: Introductionmentioning
confidence: 99%